Recent Progress in Processing of Tungsten Heavy Alloys. (28th December 2014) - Şahin, Y.
Abstract : Tungsten heavy alloys (WHAs) belong to a group of two-phase composites, based on W-Ni-Cu and W-Ni-Fe alloys. Due to their combinations of high density, strength, and ductility, WHAs are used as radiation shields, vibration dampers, kinetic energy penetrators and heavy-duty electrical contacts. This paper presents recent progresses in processing, microstructure, and mechanical properties of WHAs. Various processing techniques for the fabrication of WHAs such as conventional powder metallurgy (PM), advent of powder injection molding (PIM), high-energy ball milling (MA), microwave sintering (MW), and spark-plasma sintering (SPS) are reviewed for alloys. This review reveals that key factors affecting the performance of WHAs are the microstructural factors such as tungsten and matrix composition, chemistry, shape, size and distributions of tungsten particles in matrix, and interface-bonding strength between the tungsten particle and matrix in addition to processing factors. SPS approach has a better performance than those of others, followed by extrusion process. Moreover, deformation behaviors of WHA penetrator and depleted uranium (DU) Ti alloy impacting at normal incidence both rigid and thick mild steel target are studied and modelled as elastic thermoviscoplastic. Height of the mushroomed region is smaller forα = 0.3 and it forms sooner in each penetrator as compared to that forα = 0.2 .